Impact of Terrorist Attacks on Stock Market Performance: A Case of Pakistan - Khalil, Faisal; Akhtar, Waheed (Asian Journal of Economic Modelling, 2017)
The purpose of this study is to assess the impact of terrorist attacks on the volatility of Karachi Stock Exchange 100- index over the period from 2004 to 2014 by studying 2714 terrorism events in Pakistan. Using a series of dummy variables, this study assesses how stock market responds to terrorist events in different regions with respect to different type of attacks like, armed assaults, assassination, bomb-blast and hostage and different type of Target; military, journalists, business and education institutions. The results of the study concluded that terrorism adversely affects the stock market and increases its volatility though the stock market recovers itself after one day. Results by location confirm that event in KPK province impact, highly negatively upon KSE returns followed by Karachi. Attacks on military and journalist are giving highest negative impact on returns and hostage has a significant contribution in negative returns of KSE100 index.